The Effect of Pineapple Juice and Honey on the Acceleration of Perineal Wound Healing in Post-Partum Mothers in the Work Area of Dr. M.M. Dunda Limboto Hospital - Sri Mulyaningsih; Ratna Dunggio; Kris Ayu Susanti (Journal of Community Health Provision, 2021)
The purpose of this research is to determine the effect of pineapple juice and honey on the acceleration of perineal wound healing in puerperal mothers, with a quasi-experimental design. The research design chosen was Post Test Only Control Group Design using purposive sampling technique with a sample of 36 respondents. The experimental group 18 which was given pineapple juice and honey for 7 days was 150 ml 2x1 then measured by post-test after the treatment while the control group 18 respondents who were not given treatment. The results showed that administration of pineapple juice and honey had a significant effect on the acceleration of perineal wound healing in postpartum mothers using the Whitney mann test to obtain a mean of 24.50-12.50 mean value of 12 ρ value 0,000 <α 0.05.